Information of prostate biopsy positive core: does it affect MR detection of prostate cancer on using 3T-MRI? - Yoshida, Rika; Kaji, Yasushi; Tamaki, Yukihisa; Katsube, Takashi; Kitagaki, Hajime; Kanbara, Tsunehito; Kamai, Takao (Japanese Journal of Radiology, 2015)
Objective: We assessed which information from a prostate biopsy had the strongest relationship with prostate cancer detection by 3T-MRI.Materials and Methods: Sixty-one consecutive patients with biopsy-proven prostate cancer who underwent 3T-MRI before biopsy were enrolled in this retrospective study. Two radiologists independently reviewed T2-weighted and diffusion-weighted images. When the cancer lesions were revealed by biopsy and MRI depicted them at corresponding sites, we classified these lesions as MRI-detectable cancer. If the cancer lesions were revealed by biopsy, but any cancers had not been detected, we classified these lesions as MRI-undetectable cancer. We compared the Gleason score (GS), cancer ratio (CaR) and cancer length (CaL) from core biopsies between the two groups.the Results: GS, CaR and CaL differed significantly between the MRI-detectable group (N = 70), and the MRI-undetectable group (N = 73). 3T-MRI could detect cancer cores with a sensitivity of 90.5% in cores with CaR ≥ 60%, and with a sensitivity of 81.8% in those with CaL ≥ 5 mm. Receiver operating characteristic analysis showed that CaR (P = 0.006) and CaL (P = 0.010) significantly associated with the prostate cancer detection using MRI rather than GS.Conclusion: CaR and CaL from the core biopsies showed a stronger relationship to detection of the prostate cancer on 3T-MRI than the GS did.